Estudo sobre o impacto da redução do consumo de cimento no comportamento mecânico do concreto autoadensável - Barboza, Lucas da Silva (2016)
This paper presents an analysis of the development of self-compacting concrete with low consumption of Portland cement, and evaluates some of its properties in fresh and hardened state ( mechanical properties ). The production of concrete with low consumption of Portland cement of the concept of providing more sustainable construction based on the concrete industry, as increased longevity of raw materials deposits, reducing CO2 emissions and energy consumption and lower cost transport. It provides various technical improvements such as lower heat of hydration, shrinkage and cracking. Based on packaging concepts and particle dispersion suitable choice of materials and the use of mineral fílers and admixtures, there was obtained concrete with low consumption of cement and high strength, with a relative consumption of binder materials less than 5 kg / m³ to produce 1 MPa compressive strength. This research is characterized as a theoretical-experimental model, which were researched packaging methods of aggregates and mineral additions, studied the interaction between superplasticizer and cementitious materials, seeking a considerable reduction in cement content in mixtures of self-compacting concrete. Therefore, we used the dosage methodology presented by Gomes (2002) and also have certain mechanical properties of concrete and it is concluded by the results, the use of a structural concrete self-compacting with Portland cement consumption can reduced.